Mac OS X pocket reference - Toporek, Chuck, 1965- (O'Reilly, 2002)
Apple's new operating system, Mac OS X, is reaching a critical mass. Its sleek Aqua interface, combined with a powerful BSD Unix core, bring usability and stability to a new level. As companies start to migrate to Mac OS X from earlier versions of the Mac OS and from other flavors of Unix, IT managers are looking for a quick reference guide to get users started quickly; this Pocket Reference is that guide. The Mac OS X Pocket Reference introduces Mac, Windows, and Unix users to the fundamental concepts of Mac OS X. The book will show you how to use the Finder and the Dock, as well as how to configure your system using the System Preferences. Because Mac OS X is Unix-based, the Mac OS X Pocket Reference shows you how to issue basic Unix commands using the Terminal application. Topics covered in this book include: How to configure your Mac OS X system How to use the Finder and the Dock An overview of keyboard shortcuts for use with the GUI and the Terminal How to create special characters and symbols The book starts out with a "Mac OS X Survival Guide," which shows Mac users what's changed from Mac OS 9, and also helps Windows and Unix converts get acclimated with their new OS. The Mac OS X Pocket Reference concludes with a 30+-page "Task and Setting" index, which answers questions that users might have when trying to configure their system. This handy pocket reference is the ultimate guide for newcomers to Mac OS X, and is a great companion for use with David Pogue's Mac OS X: The Missing Manual.